Penggunaan Buku Ajar Cosmopolite 1 untuk Pembelajaran Français Langue Étrangère - Tania Intan; Vincentia Tri Handayani; Ferli Hasanah (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
Textbooks have a very important function in education because they facilitate the teaching and learning process for teachers and learners. Teaching material is considered good if it contains educational content that facilitates learners learning actively and independently. This research was conducted to evaluate the use of Cosmopolite 1 textbooks in learning French in the French Literature Study Program at Padjadjaran University. The study was conducted using a combination of quantitative and qualitative methods, and data were collected in January 2020 through filling out questionnaires and literature studies, for later review descriptively. The lecturer respondents consisted of three people who supported Basic French, while the student respondents consisted of thirty people who were chosen based on the lecturers' recommendations. The evaluation results showed that the Cosmopolite 1 was rated positively by the lecturer and student respondents. Besides, the book fulfils the criteria of self-instructional, self-contained, stand-alone, adaptive, and user friendly. The recommendation made from this research is that an evaluation should always be carried out on all elements of learning, including textbooks.